Online marketing of tourism companies : cases from Borgarfjörður, Iceland - Snorri Guðmundsson 1977- (2010)
The objective of this thesis is to study how companies that cater to tourists in Iceland use the Internet as a marketing tool. The ever-expanding usage of the Internet, both in Iceland and around the globe, makes it a very useful marketing tool since it can be used to reach people on the other side of the world with a touch of a button. But the Internet can also be quite a hindrance when in this trade. A bad review on a respected website can have a devastating effect on a company and its business. It is therefore vital for tourism companies to increase their Internet usage so they can disseminate the correct, up-to-date information to both their present and future clients. The methodology used was in the form of qualitative research that means the majority of analytical references came from interviews with owners and managers of the case companies involved. The interviews were semi-structured with a few predetermined questions and then follow-up questions as the interview went on. The study shows that the case companies use the Internet quite differently in their day-to-day operation and they emphasize on different aspects of the Internet. Some claimed a lack of knowledge and others stated that they simply did not have the time needed to use the Internet in a more productive way, but everyone seemed to realize the importance of the Internet and agreed that Internet based marketing is something that they have to implement better into their marketing mix in the near future.